Adsorption of Rare Earth Ce3+ and Pr3+ Ions by Hydrophobic Ionic Liquid. (30th May 2021) - Devanathan, R.; Balaji, G. L.; Lakshmipathy, R.
Abstract : This study reports the use of hydrophobic ionic liquid (IL) based on D-galactose for the recovery of Ce (III) and Pr (III) ions from solutions. The equilibrium data were obtained by optimization of batch parameters, and various isotherms and kinetic models were utilised to predict the mechanistic process of sequestration of ions. The Arrhenius activation energies are found to be between 5–40 kJ, suggesting the physisorption process of ions onto IL. The present process is understood to be rapid and exothermic in nature according to thermodynamic experiments. The loading capacity was found to be 179.3 g L −1 and 141.5 g L −1, respectively, for Ce (III) and Pr (III) ions at pH 5 with a contact time of 30 min and dose being 0.1 g L −1 . The higher uptake capacity is attributed to the presence of a highly electronegative fluorine atom in the IL. These results highlight the potential application of IL in the sequestration of Ce (III) and Pr (III) ions from any water sources.